Double integrating XYL2 into engineered Saccharomyces cerevisiae strains for consistently enhanced bioethanol production by effective xylose and hexose co-consumption of steam-exploded lignocellulose in bioenergy crops. (March 2022) - He, Boyang; Hao, Bo; Yu, Haizhong; Tu, Fen; Wei, Xiaoyang; Xiong, Ke; Zeng, Yajun; Zeng, Hu; Liu, Peng; Tu, Yuanyuan; Wang, Yanting; Kang, Heng; et al.
Abstract: Cellulosic ethanol has been regarded as excellent additive into petrol fuels for reduced net carbon release, and yeast fermentation is thus a crucial step for bioethanol production. In this study, three ( XYL1 / Candida tropicalis, XYL2 / Candida tropicalis, XKS1 / Saccharomyces cerevisiae) genes were isolated to construct four novel vectors using gene fusion and tandem technology. Four constructs were then transformed into common Saccharomyces cerevisiae strain, leading to varied and limited xylose utilization. While two representative constructs were transformed into industrial yeast strain (SF7), the engineered SF7-Ft3 strain could consume 95% of total xylose for ethanol yield at 2.08 g/L, whereas the control strain only utilized 13% xylose with ethanol yield at 0.56 g/L. Additional XYL2 overexpression into the SF7-Ft3 strain led to consistently enhanced xylose utilization by from diverse enzymatic hydrolats of steam-exploded lignocellulose residues in three major bioenergy crops (wheat, maize, Miscanthus ). These consequently increased bioethanol yields (% dry matter) and concentrations (g/L) by 11%–42%. Therefore, this study has demonstrated an applicable yeast-engineering approach for efficient xylose consumption and also provided a powerful strategy for enhancing bioethanol production in bioenergy crops. Graphical abstract: Image 1 Highlights: Diverse integration of XYL1, XYL2 and XKS1 for varied xylose utilizations in yeast. Engineered industrial strain (SF7-Ft3) consumed 95% xylose for yeast fermentation. XYL2 double-overexpression with SF7-Ft3 for further enhanced xylose consumption. Ethanol yield and concentration were raised at 11%–42% by SF7-Ft3-X2 strain. Integrating engineered yeast strain with steam-exploded biomass for bioethanol.